2007
DOI: 10.1584/jpestics.r07-03
|View full text |Cite
|
Sign up to set email alerts
|

Use of NMR for metabolic profiling in plant systems

Abstract: The review deals with the applications of solution state 1 H NMR to the metabolic profiling of plant tissue extracts. NMR is introduced as one of several measurement techniques that are being used in metabolomics. Samples are measured as extract mixtures without any chromatographic separation of individual compounds. Although a limited quantitative measurement of individual components is feasible, the data analysis generally relies on the application of multivariate statistical methods to the whole spectral tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 58 publications
0
34
0
3
Order By: Relevance
“…In any case where aqueous or part-aqueous solvents were employed, a 100 mM deuterated ammonium acetate buffer was introduced to reduce variance in the chemical shifts of pH-sensitive metabolites, as recommended by Colquhoun. [30] Additionally, 0.5 mM sodium azide was added as a bacteriostat [31,32] and 100 µM trimethylsilylpropionate-d 4 (TMSP-d 4 ) was utilized as a chemical shift reference. Following perchloric acid treatment (method 5), extracts were titrated to a pH meter reading of 4.76.…”
Section: Resultsmentioning
confidence: 99%
“…In any case where aqueous or part-aqueous solvents were employed, a 100 mM deuterated ammonium acetate buffer was introduced to reduce variance in the chemical shifts of pH-sensitive metabolites, as recommended by Colquhoun. [30] Additionally, 0.5 mM sodium azide was added as a bacteriostat [31,32] and 100 µM trimethylsilylpropionate-d 4 (TMSP-d 4 ) was utilized as a chemical shift reference. Following perchloric acid treatment (method 5), extracts were titrated to a pH meter reading of 4.76.…”
Section: Resultsmentioning
confidence: 99%
“…In this review we found that environmental metabolomics has been mostly applied in the study of soil health, pesticide in soil and pesticide residues using earthworm models (62,66) and metabolomics as a tool to study plant defenses and profiling (67,69). Thirty-one percent of the articles reviewed used the worm as an organism of study and 10% in plants, Figure 5b.…”
Section: Environmental Metabolomics and Bioavailabilitymentioning
confidence: 99%
“…As shown in the literature research above, this is a very well documented and widely used approach. To test the feasibility of this approach, it is subjected to a detailed review:  Analytical-scale separation and determination of molecular structure is a very well-researched area in the scientific field of substance discovery in plant extracts [40][41][42][43][44][45][46]. Nevertheless, these techniques are optimized with the focus being to identify one or at least a few substances.…”
Section: Solid-liquid-extractionmentioning
confidence: 99%